2019
DOI: 10.1177/1078155219831377
|View full text |Cite
|
Sign up to set email alerts
|

The role of the pharmacist in improving medication beliefs and adherence in cancer patients

Abstract: Background Multiple factors have been reported to affect adherence to medication, including beliefs about medicines, while specifically tailored pharmaceutical care services for patients may improve adherence. The aim was to assess the impact of counselling by an oncology pharmacist on patients' medication adherence and beliefs. Methods An interventional prospective study was performed in the oncology department at a tertiary hospital in Northern Cyprus from November 2017 to April 2018. The Beliefs about Medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…36 In addition, clinical pharmacy in hospitals has become widespread in a number of health care contexts, such as pharmaceutical instructions, intervention, evaluation and consultation (medication supply). Birand et al 6 demonstrated that counseling by an oncology pharmacist was effective in decreasing patient concerns and increasing their understanding of the necessity of the medication, thus enhancing their adherence and consequently improving the medical care they received.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…36 In addition, clinical pharmacy in hospitals has become widespread in a number of health care contexts, such as pharmaceutical instructions, intervention, evaluation and consultation (medication supply). Birand et al 6 demonstrated that counseling by an oncology pharmacist was effective in decreasing patient concerns and increasing their understanding of the necessity of the medication, thus enhancing their adherence and consequently improving the medical care they received.…”
Section: Discussionmentioning
confidence: 99%
“…They are also the principal investigators of the associated research studies. The economic and humanistic values of oncology pharmacy services have been well described [2][3][4][5][6][7][19][20][21][22] and the diagnostic value of the pharmacists' services in precision medicine with regard to training and implementation initiatives may be better evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pharmacists should work on assessing and improving patient adherence through patient educations and promote awareness of the consequences of non-adherence in CVD [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…50 Counseling from pharmacists decreases patient concerns and increases knowledge of their oncology regimen. 51 McKee et al noted that 86% of oncology patients found it important to discuss their treatment regimen with a pharmacist and 76% requested time with a pharmacist at future visits. 52 Furthermore, the role of a pharmacist in a multidisciplinary team can improve ADR monitoring and management.…”
Section: Role Of the Oncology Specialty Pharmacistmentioning
confidence: 99%